2020
DOI: 10.1038/s41467-020-15962-x
|View full text |Cite
|
Sign up to set email alerts
|

Loss of MBNL1 induces RNA misprocessing in the thymus and peripheral blood

Abstract: The thymus is a primary lymphoid organ that plays an essential role in T lymphocyte maturation and selection during development of one arm of the mammalian adaptive immune response. Although transcriptional mechanisms have been well documented in thymocyte development, co-/post-transcriptional modifications are also important but have received less attention. Here we demonstrate that the RNA alternative splicing factor MBNL1, which is sequestered in nuclear RNA foci by C(C)UG microsatellite expansions in myoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 73 publications
3
25
0
Order By: Relevance
“…Among the top 20 most statistically significant DEGs were genes associated with these processes ( Fig. 4 C), for example, Mmp14 , a membrane-bound matrix metalloproteinase involved in breakdown of the extracellular matrix ( Kessenbrock et al, 2010 ); H1f0 , an H1 linker histone necessary for the condensation of nucleosome chains into higher-order chromatin structures, which is involved in the regulation of mRNA splice site recognition ( Kalashnikova et al, 2013 ; Di Liegro et al, 2018 ); and Mbnl1 , a regulator of alternative splicing that functions in the control of T-cell development, and is overexpressed in mixed lineage leukaemia ( Ho et al, 2004 ; Wang et al, 2012 ; Sznajder et al, 2020 ; Itskovich et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the top 20 most statistically significant DEGs were genes associated with these processes ( Fig. 4 C), for example, Mmp14 , a membrane-bound matrix metalloproteinase involved in breakdown of the extracellular matrix ( Kessenbrock et al, 2010 ); H1f0 , an H1 linker histone necessary for the condensation of nucleosome chains into higher-order chromatin structures, which is involved in the regulation of mRNA splice site recognition ( Kalashnikova et al, 2013 ; Di Liegro et al, 2018 ); and Mbnl1 , a regulator of alternative splicing that functions in the control of T-cell development, and is overexpressed in mixed lineage leukaemia ( Ho et al, 2004 ; Wang et al, 2012 ; Sznajder et al, 2020 ; Itskovich et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The GO analysis also showed enrichment for several terms related to RNA splicing, and for terms connected to cell matrix adhesion (Fig 4B). Amongst the top 20 most statistically significant DEG were genes associated with these processes (Fig 4C ): for example, Mmp14, a membrane bound matrix metalloproteinase involved in breakdown of the extracellular matrix(55); H1f0, an H1 linker histone necessary for the condensation of nucleosome chains into higher-order chromatin structures, which is involved in the regulation of mRNA splice site recognition (56,57); and Mbnl1, a regulator of alternative splicing, which functions in the control of T-cell development, and is over-expressed in mixed lineage leukemia (58)(59)(60)(61).…”
Section: Foxa1 and Foxa2 Regulate Exon Usagementioning
confidence: 99%
“…For example, the SF SF3B3 is upregulated and contributes to tumorigenesis by regulating EZH2 pre-mRNA splicing, representing a key prognostic factor and therapeutic target in clear cell renal cell carcinoma (19). Similarly, many recent studies have shown that DASEs regulated by differentially expressed SFs have effects on tumorigenesis, the epithelial-mesenchymal transition, and lymphatic metastasis (12,(20)(21)(22)(23)(24). Therefore, analyses of DASEs can be meaningful in an oncogenic context.…”
Section: Discussionmentioning
confidence: 99%
“…RNA-seq con rmed the regulation of MBNL1 on the cell apoptosis signaling pathway. Some research have pointed out that MBNL1 may play an important role in the cell apoptosis (Wu et al, 2018;Sznajder et al, 2020). They pointed out that MBNL1 overexpression signi cantly decreased the proliferation rate and increased apoptosis (Wu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…MBNL1 regulates essential alternative RNA splicing patterns in MLL-rearranged leukemia (Itskovich et al, 2020). And loss of MBNL1 induces RNA misprocessing in the thymus and peripheral blood (Sznajder et al, 2020). Repression of MBNL1-dependent alternative splicing may contribute to the regulation of stem cell fates (Welte et al, 2019).…”
Section: Introductionmentioning
confidence: 99%